A facile route to prepare mixed transition metal oxide yolk–shell microspheres for enhanced lithium storage. Issue 28 (21st June 2019) - Gu, Yuanxiang; Xuan, Yuxue; Zhang, Heng; Deng, Xiaoyan; Sun, Yanhui; Wang, Lei
Abstract : Yolk–shell ZnCo2 O4 microspheres were prepared via a coordination co-precipitation route, which exhibited superior electrochemical performance. Abstract : A coordination co-precipitation route followed by a calcination process was developed to prepare mixed transition metal oxide microspheres with a yolk–shell structure. ZnCo2 O4, NiCo2 O4, MnCo2 O4, ZnMn2 O4 and CoMn2 O4 have been successfully fabricated, which demonstrates the universality of this route. As a promising anode for lithium-ion batteries (LIBs), ZnCo2 O4 was investigated as a typical example, which showed a remarkable reversible capacity of 1063 mA h g −1 after 50 cycles at a current density of 200 mA g −1 and a good rate capability of 839 mA h g −1 after 200 cycles at a large current density of 900 mA g −1 . This work shows the extensive potential of a general route for the synthesis of yolk–shell microspheres for next-generation energy conversion and storage devices.